An Analysis of the Synergistic Impact of Leadership and Stakeholder Involvement: School-Based Quality Improvement Management - Rahmad Syahbidin Ritonga; Sri Milfayetty; Arif Rahman (Randwick International of Education and Linguistics Science Journal, 2024)
This research aims to analyze the synergistic impact between school leadership and stakeholder involvement in efforts to improve the quality of education at the Al Hijrah Integrated Islamic Middle School, Deli Serdang. A descriptive quantitative approach was used as a research method, and data was collected using questionnaires from respondents, namely the school principal and all school stakeholders. The results of the research show that school leadership that is synergistic and involves school stakeholders has a great influence on the management of improving school quality. Strong leadership and active stakeholder involvement have a significant positive impact on school-based quality improvement management. Visionary and learning-oriented leadership plays a key role in formulating a shared vision and strategy to improve the quality of education. The involvement of stakeholders, including teachers, parents, and the community, provides support, input, and active participation in the implementation of quality improvement programs. The synergy between effective leadership and involving stakeholders can create a collaborative and supportive learning environment. This leads to achieving the goals of better quality education, improving the quality of learning, and holistic development of student potential.